lntracycle kinematics and body configuration changes in the breaststroke - Kent, M. R.; Atha, J. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
Developing high quality competitive performance in swimming, as in any other skilled activity, requires more than intensive and intelligently directed practice: it requires information. At best this information will include details of the way in which the many different movements of the swimmer produce changes in his swimming speed. In this investigation an attempt was made to provide a detailed description of the intracycle kinematics of one top class breaststroke swimmer and to associate these with the body configuration changes which accompanies them.